Radiation-Induced Oral Mucositis - Maria, Osama Muhammad; Eliopoulos, Nicoletta; Muanza, Thierry (Frontiers in Oncology, 2017)
Radiation-induced oral mucositis (RIOM) is a major dose-limiting toxicity in Head and Neck cancer patients. It is a normal tissue injury caused by radiation/radiotherapy (RT), which has marked adverse effects on patient quality of life and cancer therapy continuity. It is a challenge for radiation oncologists since it leads to change in dose fractionation, cancer therapy interruption, and poor local tumor control. RIOM occurs in 100% of altered fractionation radiotherapy Head and Neck cancer patients. At the USA, its economic cost was estimated to reach $ 17,000.00 USD per patient with Head and Neck cancers. This review will discuss RIOM definition, epidemiology, impact and side effects, pathogenesis, different scoring scales, diagnosis, differential diagnosis, prevention and treatment.